GRP-017 Analysis and Prevention of Musculoskeletal Disorders in a Hospital Sterilisation Unit. (12th March 2013) - Tortolano, L; Becamel, I; Briand, D; Vincent, F
Abstract : Background: Musculoskeletal disorders (MSDs) are problems caused by the poor ergonomic design of work stations. The daily work of sterilisation, especially carrying heavy loads, carries a risk of developing MSDs. Our sterilisation unit, certified ISO 9001, tries to improve the working environment including the ergonomics of work stations. Purpose: To establish an inventory of fixtures and to suggest preventive measures in order to limit the appearance of those disorders. Materials and Methods: The whole of the sterilisation unit workforce was interviewed about any pain, physical effort and non-ergonomic situations that they routinely face during their daily work. Results: The main pain reported by the staff was lumbar pain (70%). Several factors explain that result: Repeatedly carrying heavy weights (>7 Kg), especially when loading the Instrument Washer-Disinfector trolleys and sterilisers. Making little use of helping fork-lift trucks (60% of the staff use them <2 hrs/day). Not asking colleagues for help when carrying heavy weights. 80% of people work in front of a computer screen for 1/3 or ½ the day without adopting an ergonomic position. Highly repetitive actions during packaging. Preventive measures: Staff training on ergonomics suited to any post. Organization of packaging posts and data capture according to the "comfort zone" concept. Reduction of distances to be covered when carrying or moving heavy weights. Conclusions: This study demonstrates that MSDs often app eared in sterilisation. The implementation of suitable preventive measures – according to posts – should increase efficiency and reduce the physical demands made on members of staff. No conflict of interest.